A Fatal Case of Bacteremia Caused by Vibrio cholerae Non-O1/O139 - Hwang, Soyoon; Kim, Yoonjung; Jung, Hyejin; Chang, Hyun-Ha; Kim, Su-Jeong; Park, Han-Ki; Lee, Jong-Myung; Kim, Hye-In; Kim, Shin-Woo (Infection & chemotherapy, 2021)
is a pathogen known to cause the waterborne epidemic disease cholera. Overall, O1 or O139 strains produce the cholera toxin that cause gastroenteritis, resulting in watery diarrhea. Most of the enterocolitis caused by can be easily treated with fluid therapy and conservative care. However, non-O1/O139 strains can cause extraintestinal infections, such as wound infection or sepsis, in immunocompromised patients. The clinical course of these infections is very similar to that of infection. We report about a 52-year-old man without previous underlying disease who was diagnosed with non-O1/O139 infection and died within 72 hours after admission to the intensive care unit.